Modulating drug release from poly(lactic‐co‐glycolic) acid microparticles by the addition of alginate and pectin. Issue 17 (25th November 2020) - Karp, Federico; Satler, Florencia S.; Busatto, Carlos A.; Luna, Julio A.; Estenoz, Diana A.; Turino, Ludmila N.
Abstract: The aim of the present work is the characterization of PLGA microparticles including biopolymers for the controlled release of tilmicosin, a broad‐spectrum antibiotic. Microparticles were prepared using the double‐emulsion solvent evaporation technique. The effect of alginate and pectin incorporation over particle size and porosity, encapsulation efficiency (EE) and pH‐responsive drug release was evaluated. Formulations presented a mean particle size of 5.5 μm approximately and a drug EE ranged from 22%–57%. PLGA‐Alginate particles showed an increased porosity. Tilmicosin release profiles from PLGA and PLGA‐biopolymer microparticles were affected by the particular combination of polymers and the pH of the release medium. The experimental data was simulated using a mathematical model, which takes into account the autocatalytic polymer degradation and the different mechanisms of drug transport. The combination of PLGA and biopolymers strongly influenced the morphology of the particles, offering the possibility of controlling the drug release profiles according to the therapy. Abstract :